Dynamic consistent alpha-maxim expected utility - Patrick Beißner; Qian Lin (Bielefeld University, Center for Mathematical Economics (IMW), 2015)
We establish a class of fully nonlinear conditional expectations. Similarly to the usage of linear expectations when a probabilistic description of uncertainty is present, we observe analogue quantitative and qualitative properties. The type of nonlinearity captures the agents sentiments of optimism and pessimism in an ambiguous environment. We then introduce an expected utility under a nonlinear expectation, and show monotonicity and continuity of utility. Risk aversion is characterized, and the properties of the certainty equivalent are discussed. Finally, we derive an Arrow-Pratt approximation of the static certainty equivalent and investigate the dynamic version via recursive equations.
urn:nbn:de:0070-pub-27189099
Keywords: C60; D81; D90; 330; nonlinear expectation; Knightian Uncertainty; time consistency; risk aversion; certainty equivalent; optimism and pessimism